Mixed-meta Method Concerning the Effect of Blended Learning Practices on Students' Academic Achievement in Higher Education Settings - Bingolbali, Abdullah; Aslan, Aydin; Batdi, Veli; Cinkara, Emrah (Sage Publications Inc, 2025)
This study examines the effect of blended learning (BL) practices on students' academic achievement in higher education settings through meta-analysis and meta-thematic analysis based on the data derived from document analysis. To comprehensively understand the effect of BL practices on students' achievement in higher education settings, the independent (BL), dependent (students' academic achievement), and moderator variables (school subjects, duration of implementation, and sample size) were considered. Forty-nine studies were analyzed in meta-analysis thanks to CMA and MetaWin software programs. The meta-analysis indicated that the practices affect learners' academic achievement positively. On the other hand, 20 studies were examined in the meta-thematic analysis with the Maxqda-11 software program. The meta-thematic analysis revealed four themes, namely effects of BL settings on achievement,social contributions of BL settings,general characteristics of BL settings, and negative characteristics of BL settings. The meta-analyses and the meta-thematic analyses revealed that BL practices positively affect students concerning academic sense in educational settings. Some suggestions were made to overcome the shortcomings of BL practices in education.
Keywords: blended learning practices; meta-analysis; meta-thematic analysis; mixed-meta method